2012
DOI: 10.1152/ajplung.00050.2012
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin is an endogenous modulator of the constitutively activated phenotype of pulmonary adventitial fibroblasts in hypoxic pulmonary hypertension

Abstract: Osteopontin is an endogenous modulator of the constitutively activated phenotype of pulmonary adventitial fibroblasts in hypoxic pulmonary hypertension. Am J Physiol Lung Cell Mol Physiol 303: L1-L11, 2012. First published May 11, 2012; doi:10.1152/ajplung.00050.2012.-Increased cell proliferation and migration, of several cell types are key components of vascular remodeling observed in pulmonary hypertension (PH). Our previous data demonstrate that adventitial fibroblasts isolated from pulmonary arteries of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 72 publications
2
43
0
Order By: Relevance
“…This pathway specificity is further supported by the fact that blocking a v b 3 , but not CD44, could inhibit osteopontin-induced motility of fibroblasts. Indeed, a v b 3 was shown to contribute to osteopontin-induced fibroblast motility (45).…”
Section: Discussionmentioning
confidence: 99%
“…This pathway specificity is further supported by the fact that blocking a v b 3 , but not CD44, could inhibit osteopontin-induced motility of fibroblasts. Indeed, a v b 3 was shown to contribute to osteopontin-induced fibroblast motility (45).…”
Section: Discussionmentioning
confidence: 99%
“…19 Moreover, increased OPN expression has been documented in the lungs of chronically hypoxic calves and monocrotaline-treated rats. 20,21 We found that senescent cells stimulated the growth and migration of target PA-SMCs through 2 mechanisms, that is, the release of soluble factors and the release of ECM components. In our study, cell proliferation and migration in response to culture media from senescent cells or to matrix deposited by senescent cells were markedly reduced in the presence of neutralizing anti-OPN antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Significant “imprinted” phenotypic differences have been reported in pulmonary AF derived from pulmonary hypertensive versus control animals, including far greater proliferative responses to pro-mitogenic stimuli including hypoxia, changes in the signaling pathways that elicit proliferation (18), and a marked pro-inflammatory phenotype characterized by increased production of chemokines, cytokines, matricellular proteins, and adhesion molecules (19, 20). Das et al have described significant changes in the functional role of the atypical PKCζ isozyme, such that it acted as a pro-proliferative kinase for AF from chronically hypoxic pulmonary hypertensive animals as opposed to its anti-proliferative actions in fibroblasts from normoxic controls (18).…”
Section: Adventitial Fibroblast - a “Sentinel Cell”mentioning
confidence: 99%